Mechanics of Machines - V. Ramamurti (Alpha Science Intl Ltd, 2007)
Emphasizing the industrial relevance of the subject matter, dispenses with conventional inaccurate graphical methods used in Kinematics of plane mechanisms, cams and balancing. Instead presents general vector approach for both plane and space mechanisms. New to the Second Edition · Elegant vector approach to the kinematic analysis including Coriolis acceleration · Easy vector approach to input torque estimation of planar mechanisms in place of analysis link by link · Grubbler’s criterion and its application to epicyclic gear trains · Challenging problems in epicyclic gear trains · Significance of speed in machines classifying low, medium and high speed categories Addition of 50 pages including 30 new interesting problems of industrial relevance with solutions.